IMPLEMENTATION OF LAW ON THE RIGHT TO HEALTH SERVICES FOR PRISONERS : A CASE STUDY AT CLASS IIB PRAYA DETENTION CENTER - Lalu Arafath Gymnastiar Rahman; Hidayat, Syamsul; Ardiansyah, Ruli (Parhesia, 2024)
This study, titled Implementation of Law on the Right to Health Services for Prisoners : A Case Study at Class IIB Praya Detention Center, aims to determine whether prisoners' rights to health services are stipulated in the relevant laws and regulations, and how the implementation of the fulfilment of prisoners' health service rights is carried out at Class IIB Praya Detention Center. The research employs both empirical and normative methods, utilizing legislative, conceptual, and sociological approaches. The findings indicate that the right to health services for prisoners is indeed regulated in the existing legal framework. However, the fulfilment of these health service rights at Praya Detention Center has not been fully achieved. The lack of adequate health facilities negatively impacts the health and well-being of prisoners. This limitation often leads to insufficient access to necessary medical care, an increased risk of disease transmission, and a reduced quality of life for inmates. These issues may be attributed to inadequate infrastructure, a shortage of medical personnel, and budgetary constraints. Keywords: Right to Health Services, Prisoners, Detention Center.